2009
DOI: 10.1137/070698348
|View full text |Cite
|
Sign up to set email alerts
|

Low-End Uniform Hardness versus Randomness Tradeoffs for AM

Abstract: Abstract. Impagliazzo and Wigderson [Proceedings of the 39th Annual IEEE Symposium on Foundations of Computer Science, IEEE Computer Society, Washington, DC, 1998, pp. 734-743] proved a hardness versus randomness tradeoff for BPP in the uniform setting, which was subsequently extended to give optimal tradeoffs for the full range of possible hardness assumptions (in slightly weaker settings). Gutfreund, Shaltiel, and Ta-Shma [Comput. Complexity, 12 (2003), pp. 85-130] proved a uniform hardness versus random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…This is a uniform analogue of the "low-end" nonuniform result in Such a result is known if we replace EXP by PSPACE [397]. For derandomizing AM instead of BPP, both high-end and low-end uniform results have been obtained [195,358]. These results utilize hard functions in E, unlike the nonuniform results which only require hard functions in NE ∩ co-NE (cf.…”
Section: Derandomization Vs Lower Boundsmentioning
confidence: 90%
“…This is a uniform analogue of the "low-end" nonuniform result in Such a result is known if we replace EXP by PSPACE [397]. For derandomizing AM instead of BPP, both high-end and low-end uniform results have been obtained [195,358]. These results utilize hard functions in E, unlike the nonuniform results which only require hard functions in NE ∩ co-NE (cf.…”
Section: Derandomization Vs Lower Boundsmentioning
confidence: 90%
“…Such a result is known if we replace EXP by PSPACE [397]. For derandomizing AM instead of BPP, both high-end and low-end uniform results have been obtained [195,358]. These results utilize hard functions in E, unlike the nonuniform results which only require hard functions in NE ∩ co-NE (cf.…”
Section: Derandomization Vs Lower Boundsmentioning
confidence: 99%
“…Prior to Parvaresh-Vardy codes, constructions of this type were used for extractors and pseudorandom generators. Specifically, Miltersen and Vinodchandran [289] show that if we take f to describe a multivariate polynomial (via low-degree extension) and evaluate it on the points of a random axis-parallel line through y, we obtain a hitting-set generator construction against nondeterministic circuits (assuming f has appropriate worst-case hardness for nondeterministic circuits); this construction has played a key role in derandomizations of AM under uniform assumptions [195,358]. 5 Ta-Shma, Zuckerman, and Safra [384] showed that a similar construction yields randomness extractors with seed length (1 + O( 1)) log n for polynomially small min-entropy and polynomial entropy loss.…”
Section: Algebraic Pseudorandomnessmentioning
confidence: 99%
“…We remark that in addition to uniform hardness versus randomness tradeoffs for derandomizing BPP, there is also research on uniform hardness versus randomness tradeoffs for derandomizing the class AM of "Arthur-Merlin games" [GSTS03,SU09].…”
Section: Uniform Hardness Versus Randomness Tradeoffsmentioning
confidence: 99%